Constitutional Complaint di Mahkamah Konstitusi Republik Indonesia - Agsel Awanisa; Yusdianto Yusdianto; Siti Khoiriah (Fakultas Hukum Universitas Lampung, 2021)
The purpose of this research is to determine the constitutional complaint mechanism based on comparisons in other countries, practices, and adaptation of constitutional complaints under the authority of the Constitutional Court of the Republic of Indonesia. Many cases with constitutional complaint substance have been submitted to the Constitutional Court of the Republic of Indonesia even though they don’t have this authority. This research uses a normative legal research method using a statutory approach, a conceptual approach, a comparative approach, and a case approach. This research indicates that the constitutional complaint mechanism in Germany, South Korea, and South Africa has been well implemented. In practice, cases with constitutional complaint substance are filed to the Constitutional Court of the Republic of Indonesia by changing the form by using the legal means of a judicial review, such as case number 16/PUU-VI/ 2008, case number 140/PUU-XIII/2015 and case number 102/PUU-VII/2009. Due to the consideration of the structure, substance, and culture of law, adaptation of constitutional complaint within the authority of the Constitutional Court of the Republic of Indonesia needs to be carried out by amending Law Number 24 of 2003 jo. Law Number 7 of 2020 concerning the Constitutional Court.